Eco-technique Of Sewer Renovation Using Composite Shells: Structural Analysis - Attaf, B. (University of Eloued جامعة الوادي, 2011)
An eco-technical renovation of the sewage system is developed in this paper; this technique involves incorporating into the existing sewer a series of jointed prefabricated sandwich or composite shells. The purpose of his study is to determine the structural shell deflection, the high displacement areas and to validate the non-failure criterion for each ply constituting the inner and outer laminate facings. The numerical results were obtained at low cost by using the finite element method. Studies have focused on structural analysis of a typical shell unit with an ovoid form (egg-shaped section) when it is subjected, during annular space filling operation, to pressure forces generated by wet concrete. To ensure the safety of the composite shell structure, Tsai-Hill criterion function is applied and results are presented for the most stressed plies.
Articale in Journal of fundamental and Applied Sciences Vol. 03 N. 02
Keywords: sanitation; sustainable development; composite collector en composite; sandwich shell; finite element approach.